ANALISIS PENGARUH STRATEGI HARGA, PROMOSI DAN KEPUASAN PELANGGAN TERHADAP VOLUME PENJUALAN, MINAT BELI KONSUMEN SEBAGAI MODERASI PADA CV. HOLIYEAY INDUSTRI PARFUM INDONESIA - Yumenson Blegur; Ahmad Subagyo (Sekolah Tinggi Ilmu Ekonomi GICI, 2026)
Marketing and sales management in various Indonesia companies in the Industry 4.0 era In the era of Industry 4.0, the development of digital technology encourages companies to increase the effectiveness of marketing and sales strategies to maintain competitiveness. This study aims to analyze the influence of pricing strategies, promotions, and customer satisfaction on sales volume with consumer buying interest as a moderation variable on CV. Holiyeay Indonesian Perfume Industry. The study used a quantitative approach with a sample of 222 respondents determined using the Slovin formula. Data analysis was carried out using Structural Equation Modeling (SEM) based on SmartPLS 4. The results of the study show that pricing strategies, promotions, customer satisfaction, and consumer buying interest have a positive and significant effect on sales volume (p < 0.05). In addition, the combination of pricing, promotion, and customer satisfaction strategies also has a significant influence on sales volume. Consumer buying interest has been shown to moderate the relationship between pricing strategies, promotions, and customer satisfaction to sales volume. An Adjusted R-Square value of 0.757 indicates that the model is able to explain 75.7% of the variation in sales volume, while 24.3% is influenced by other factors outside of the study